Image De-Noising techniques: a comparative study - abdulwahab, Nawafil; Taha Alshaikhli, Imad Fakhri (Design for Scientific Renaissance, 2020)
Image processing techniques can be used to distinguish images or enhance its quality. The occurrence of noises is common during electronic transmissions between devices, and the restoration of the images damaged during these transmissions is a challenging endeavor. This paper detail noises that are present in corrupt images and noise reduction techniques that can be used to minimize or eliminate noises from the images. Additionally a comprehensive survey is provided and summarises the recent implemented noise reduction techniques for noise removal from images and based of quality preservation purposes. This visualization will assist the development process of new techniques.